Design and Development of an Interactive Audit Analytics Dashboard for Higher Education Quality Assurance - Nana Fauziyah; Agus Sifaunajah (SAINTEKBU, 2026)
Many higher education institutions still conduct internal quality audits manually using separate spreadsheets, which leads to fragmented data management, delays in reporting, and reduced monitoring effectiveness. This study develops a web‑based interactive dashboard designed to organize audit information more efficiently and clearly for stakeholders. Using the Waterfall methodology requirements analysis, system design, implementation, and black‑box testing the system successfully displays quality indicators, follow‑up status, and audit progress in real time. The dashboard improves data compilation efficiency, minimizes human errors, and accelerates information distribution to institutional leaders. Usability evaluation of the system using the System Usability Scale (SUS) with 30 stakeholders yielded an average score of 81.2, indicating 'Excellent' usability and high user acceptance. Quantitative results show that the dashboard reduces audit data compilation time by 75% and provides real-time information access, thereby serving as an effective tool for monitoring and evaluating internal audit activities while supporting transparency, accountability, and data‑driven decision‑making. Future work may include integrating the dashboard with existing campus information systems and adding advanced analytics features for continuous quality improvement.